2016
DOI: 10.1177/0956462416677916
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors for increased gonorrhoea re-infection in men who have sex with men attending a genitourinary clinic: a qualitative study

Abstract: Investigating factors for increased gonorrhoea re-infection in men who have sex with men attending a genitourinary clinic: a qualitative study Copyright and reuse:Sussex Research Online is a digital repository of the research output of the University.Copyright and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable, the material made available in SRO has been checked for eligibility before being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…The most frequent STIs recorded were gonorrhoea (23 citations; prevalence reported in chemsex-related drug users was 3.9%–100% 12,14–17,20,22,26,29,32,56,77,78,80,82,84,86,87,92,98,103–105 ) and syphilis (16 citations; prevalence reported in chemsex users was 3.6%–100% 12,14–16,23,24,26,51,61,77,80,85,86,98,103,106 ). In a systematic review, Rajasingham et al 86 identified HIV-infected MSM who had used crystal methamphetamines in the prior 3 months to have a significantly higher chance of being diagnosed with an STI (gonorrhoea, chlamydia or syphilis) in the past year, compared to HIV-infected MSM who had not used crystal methamphetamine (OR = 3.37, 95% CI: 1.67–6.81).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent STIs recorded were gonorrhoea (23 citations; prevalence reported in chemsex-related drug users was 3.9%–100% 12,14–17,20,22,26,29,32,56,77,78,80,82,84,86,87,92,98,103–105 ) and syphilis (16 citations; prevalence reported in chemsex users was 3.6%–100% 12,14–16,23,24,26,51,61,77,80,85,86,98,103,106 ). In a systematic review, Rajasingham et al 86 identified HIV-infected MSM who had used crystal methamphetamines in the prior 3 months to have a significantly higher chance of being diagnosed with an STI (gonorrhoea, chlamydia or syphilis) in the past year, compared to HIV-infected MSM who had not used crystal methamphetamine (OR = 3.37, 95% CI: 1.67–6.81).…”
Section: Resultsmentioning
confidence: 99%
“…Of particular importance are local genital tract inflammatory processes that increase HIV shedding in semen rendering an individual more infectious than is apparent from his blood plasma viral load (Kalichman, Diberto, & Eaton, 2008;Pilcher et al, 2006). Thus, increases in condomless anal sex and exposure to STI will ultimately diminish the prevention benefits of HIV treatments (Jansen, Schmidt, Drewes, Bremer, & Marcus, 2016;Katz, Dombrowski, Bell, Kerani, & Golden, 2016;Payne, Lawrence, Soni, Llewellyn, & Dean, 2016;Sood, Wagner, Jaycocks, Drabo, & Vardavas, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Twelve review papers which did not provide any new data were excluded. Two further papers 2018Commentary Netherlands Bourne et al (2015) In-depth interviews England Bourne et al (2014) In-depth interviews UK Bjerno 2017Semi-structured interviews Denmark Bracchi et al 2015Commentary United Kingdom Chung et al (2015) Case Report United Kingdom Dolengevich-Segal et al, 2016Case report Spain Deimel et al (2016) In-depth interviews Germany DĂĄvila (2016) Ethnographic study Spain Elliot et al 2017Prospective opt out United Kingdom Frankis et al, 2018 Cross-sectional online survey Scotland Frankis and Clutterbuck (2017) Commentary United Kingdom Frederick (2016) Ethnography/critical discourse analysis England Gilbart and Gobin (2013) Semistructured in-depth quantitative interviews England Giraudon et al 2018 2018Case Study Australia Page and Nelson (2016) Commentary England Payne et al, (2017) In-depth semistructured interviews Ausralia Power et al 2018Cross-sectional survey Australia Pufall et al 2018Cross-sectional survey England Ralphs, Gray, and Norton 2017 meeting the inclusion criteria were identified through a hand search, yielding a total of 53 papers for critical appraisal (See Figure 1). Specific information including author, year of publication, methodology, and study location were noted (See Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a French cross-sectional survey, chronic HCV prevalence of 10.6% was reported in a population of MSM engaging in SIDU (Vaux et al, 2019). Further harms that may appear include abscesses; phlebitis; track marks and muscle damage (Knoops et al, 2015;Payne et al, 2017). Prolonged use may lead to delusional thoughts; paranoid ideation; hallucinations and suicidal ideation (Dolengevich-Segal et al, 2016) which can be exasperated by long sessions with little sleep and poor nutrition (Bourne et al, 2014).…”
Section: Health Harmsmentioning
confidence: 99%